White Rot of Korean Wild Chive Caused by Stromatinia cepivora - Wan-Gyu Kim; Gyo-Bin Lee; Hong-Sik Shim; Weon-Dae Cho (Research in Plant Disease, 2023)
In May 2020, we surveyed disease occurrence on vegetables grown in Seosan area, Korea. During the disease survey, white rot symptoms were observed in Korean wild chive (Allium monanthum) plants growing in fields. The symptoms occurred mainly in the seed bulb-producing fields of the crop. The above ground parts of the diseased plants displayed premature yellowing and dying of older leaves and stunting of the plants. The bulbs and roots of the diseased plants turned black and rotted. The disease occurred in a range of 1–60% in four of the eight fields surveyed. Three isolates of Sclerotium sp. were obtained from the bulb lesions of diseased plants. All isolates were identified as Stromatinia cepivora based on the morphological characteristics and phylogenetic analysis. Pathogenicity of the isolates on Korean wild chive was confirmed by artificial inoculation test. The lesions induced by the inoculation test were similar to those observed in the investigated fields. This is the first report of S. cepivora causing white rot in Korean wild chive.